Refugee Protection in Post-Pandemic Era: A Challenge to Reach Resilience - Kusumo, Ayub Torry Satriyo; Aziz, Sannia (Brawijaya Law Journal, 2025)
In the post-pandemic era, refugees are the most vulnerable group requiring global attention and protection of the fundamental rights. Despite the importance of safeguarding these rights, refugees often face fragile living conditions and uncertain legal status, which limit the ability to prioritize health and well-being. Persistent challenges such as status determination processes, safe third-country agreements, and the growing impact of climate change have further intensified these vulnerabilities. Therefore, this study aimed to examine the intersection of refugee protection, public health, and climate change to identify strategies for enhancing resilience in post-pandemic contexts. By using a qualitative narrative review of academic, legal, and policy literature, the analysis fostered a comprehensive and critical discussion of the issues. The results suggested that the complexity of these challenges left developing countries in the global North, often transit hubs for migrants, unable to address the problems independently. Addressing the issues effectively required cooperative regional efforts and innovative policymaking. Furthermore, this study contributed to the discourse on sustainable and inclusive strategies for addressing global challenges affecting refugee populations.